Posted by **kozy** on Sunday, May 1, 2011 at 5:22pm.

In solving the equation (x + 3)(x + 1) = 48, Eric stated that the solution would be

x + 3 = 48 => x = 45

or

(x + 1) = 48 => x = 47

However, at least one of these solutions fails to work when substituted back into the original equation. Why is that? Please help Eric to understand better; solve the problem yourself, and explain your reasoning.

## Answer This Question

## Related Questions

- Algebra - In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
- algebra - 1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
- math - In solving the equation (x + 4)(x – 7) = -18, Eric stated that the ...
- intermediate algebra - In solving the equation (x-1)(x+2)=30. Eric stated that ...
- South - In solving the equation (x + 1)(x – 2) = 54, Eric stated that the ...
- algebra - solving the equation (x+4)(x-4)=9 Eric stated that the solution would ...
- Math - I don't understand how to solve this problem: In solving the equation (x...
- intermediate algebra - in solving the equation (x+4)(x-4)=9 eric stated the ...
- algebra - in solving the equation (x +2)(x - 2) = 32 eric stated the solution to...
- Math - In solving the eqaution(x+4)(x-4),Eric stated thatthe solution would be x...

More Related Questions